Profiling the Nutritional, Phytochemical, and Functional Properties of Mung Bean Varieties - Fekiya Mohammed Idris; Kelbessa Urga; Habtamu Admassu; Eskindir Getachew Fentie; Sook-Min Kwon; Jae-Ho Shin (Foods)
The Ethiopian Agricultural Research Institute (EARI) adopted four mung bean varieties for cultivation, following extensive research on their adaptability, productivity, and drought tolerance. However, the physicochemical, techno-functional, and antioxidant properties of these cultivars, which can vary significantly due to genetic and agro-ecological differences, have not been sufficiently explored in previous research. Hence, this study aimed to elucidate these properties to facilitate their seamless integration into food formulation and product development. The study results revealed that the protein content of these varieties ranged from 22.63 to 25.84 g/100 g, while carbohydrate content ranged from 54.9 to 58.82 g/100 g. Moreover, all examined varieties exhibited elevated levels of essential amino acids, particularly lysine, phenylalanine, and leucine. The foaming capacity and emulsion activity varied between 40.27–49.2% and 52.75–54.13%, respectively. The loss modulus of all varieties surpassed the storage modulus. Total polyphenol and flavonoid contents ranged from 2.36 to 3.05 mg GAE/g and 1.42 to 2.22 mg QE/g, respectively. The antioxidant activities were assessed using different assays and revealed that all samples were concentration-dependent, with all cultivars exhibiting high antioxidant activity at higher concentrations. The comparative analysis of the examined varieties revealed that none excelled in all of the tested parameters. However, these diverse qualities make Ethiopian mung bean varieties suitable for various food formulations tailored to specific desired characteristics.